2020
DOI: 10.1080/23744235.2020.1806353
|View full text |Cite
|
Sign up to set email alerts
|

Previous and active tuberculosis increases risk of death and prolongs recovery in patients with COVID-19

Abstract: Background: There is a growing literature on the association of SARS-CoV-2 and other chronic conditions, such as noncommunicable diseases. However, little is known about the impact of coinfection with tuberculosis. We aimed to compare the risk of death and recovery, as well as time-to-death and time-to-recovery, in COVID-19 patients with and without tuberculosis. Methods: We created a 4:1 propensity score matched sample of COVID-19 patients without and with tuberculosis, using COVID-19 surveillance data in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
108
3
15

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(129 citation statements)
references
References 14 publications
3
108
3
15
Order By: Relevance
“…49,50 Previously published studies regarding COVID-19 have revealed that the presence of tuberculosis was associated with higher severity and mortality from COVID-19. 51,52 Secondly, some proportions of PLWH may have incomplete immune reconstitution and evidence of persistent immune activation. 53 They may show an abnormal innate and adaptive immune response, characterised by the elevation of macrophages, cytokines [tumour necrosis factor alpha, interleukin (IL)-1, IL-6, IL-8 and IL-10], acute phase proteins [serum amyloid A, C-reactive protein (CRP)], elements of the coagulation cascade (D-dimer and tissue factor), increased turnover and exhaustion of T cells, increased turnover of B cells and hyperimmunoglobulinaemia.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 Previously published studies regarding COVID-19 have revealed that the presence of tuberculosis was associated with higher severity and mortality from COVID-19. 51,52 Secondly, some proportions of PLWH may have incomplete immune reconstitution and evidence of persistent immune activation. 53 They may show an abnormal innate and adaptive immune response, characterised by the elevation of macrophages, cytokines [tumour necrosis factor alpha, interleukin (IL)-1, IL-6, IL-8 and IL-10], acute phase proteins [serum amyloid A, C-reactive protein (CRP)], elements of the coagulation cascade (D-dimer and tissue factor), increased turnover and exhaustion of T cells, increased turnover of B cells and hyperimmunoglobulinaemia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, with the recent pandemic of COVID-19, several studies have come forth regarding the coinfection of TB with COVID-19 with the first set of studies suggesting the synergistic potential of COVID-19 with TB worsening prognosis of TB patients [4][5].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Moreover, as of October 2020, cases have been steadily increasing in South Africa. 6,7 A number of factors facilitate increased COVID-19 transmission in Africa, including weak health care systems, 8 high prevalence of other diseases such as HIV and TB, [9][10][11][12] and the inability to adhere to physical distancing and other intervention strategies. 13 Although the current reported mortality burden is lower than had been projected by public health experts, the pandemic has highlighted gaps in surveillance systems.…”
Section: Introduction (1473 Words)mentioning
confidence: 99%
“…4,5 Moreover, as of October 2020, cases have been steadily increasing in South Africa. 6,7 A number of factors facilitate increased COVID-19 transmission in Africa, including weak health care systems, 8 high prevalence of other diseases such as HIV and TB, 9-12 and the inability to adhere to physical distancing and other intervention strategies. 13…”
Section: Introductionmentioning
confidence: 99%